Agreement between a motorized resistance device and traditional systems for sprint and change-of-direction testing in female volleyball players - Wright, W. C.; Aguiar, E. J.; Winchester, L. J.; Fedewa, M. V.; Esco, M. R. (The Journal of Strength and Conditioning Research, 2026)
The purpose of this study was to determine the agreement between a motorized sprint resistance device (MSRD) and timing gates and an inertial measurement unit (IMU), for assessing time to completion and peak velocity during linear and change-of-direction tasks in elite female volleyball players. Elite volleyball athletes (n = 16, 19.4 ± 1.5 years, 176.2 ± 10.6 cm, 71.5 ± 11.1 kg) performed the 18.29 m sprint and 5-10-5 drills while being simultaneously assessed using an MSRD, timing gates, and an IMU. Compared with timing gates for measuring sprint (3.09 ± 0.16 seconds) and 5-10-5 (5.08 ± 0.19 seconds) time, the MSRD showed significant (p < 0.01) mean differences (3.15 ± 0.17 seconds [p < 0.01, Cohen's d = 0.49, small]) and 5.16 ± 0.21 seconds [p < 0.01, Cohen's d = 1.14, moderate], respectively, but the correlations were very large to nearly perfect (r = 0.97 and 0.87, respectively). Limits of agreement (LOA) for sprint time were -0.10 ± 0.10 seconds and for 5-10-5 time were 0.23 ± 0.24 seconds. For peak velocity, the mean values from MSRD and IMU for the sprint (4.62 ± 0.34 m·s-1 and 4.72 ± 0.44 m·s-1, respectively [p = 0.78]) and 5-10-5 drill (3.91 ± 0.47 m·s-1 and 3.93 ± 0.50 m·s-1, respectively [p = 0.98]) were not significantly different. The correlation between the peak velocity values was significant for the sprint (r = 0.65, p < 0.01), but not for 5-10-5 (r = 0.25, p = 0.69), with LOA values of 0.03 ± 0.86 m·s-1 and 0.00 ± 0.98 m·s-1, respectively. The MSRD seems to agree with timing gates for sprint and 5-10-5 time. However, the agreement with IMU for peak velocity is weaker.